Characteristics of infants with positional abnormal head shapes and their physiotherapy service at an Australian community health facility - Leung A; Watter P; Gavranich J (Dove Medical Press, 2014)
Amy Leung,1 Pauline Watter,2 John Gavranich31Department of Physiotherapy, Royal Children's Hospital, 2Physiotherapy Division, School of Health Rehabilitation Science, The University of Queensland, Brisbane, Queensland, Australia; 3Child and Family Health Services, West Moreton Health Service District, Queensland, AustraliaPurpose: There is limited biographic information regarding infants presenting with abnormal head shape in Australia and little discussion of the effect of different cutoff values for diagnosis of plagiocephaly. This study aimed to 1) describe the biographic characteristics of infants with positional abnormal head shapes referred for physiotherapy management; 2) explore their access to physiotherapy services and intervention outcomes; and 3) explore the impact of using different modified Cranial Vault Asymmetry Index (mCVAI) cutoff points in plagiocephaly classification.Patients and methods: This retrospective community health record audit included the total cohort of infants referred over concerns about abnormal head shape to a pediatric physiotherapy service at a community health center in Australia from January 2004 to December 2007 (N=126 valid cases). Data retrieved included: demographic data; birth history; positioning; initial physiotherapy assessment; and factors associated with physiotherapy intervention and outcomes.Results: Of the 126 charts (65 males), 106 infants (84.1%) presented with plagiocephaly, ten (7.9%) with brachycephaly, and ten (7.9%) with combined deformities. Most biographic data from this study were similar to those reported in the literature. The mean age ± standard deviation (SD) of infants at referral was 11.29±7.84 weeks, with about 4-weeks wait for assessment. For the plagiocephalic group, there was significant reduction in mCVAI mean value from assessment (-5.44%±2.95%) to discharge (-4.41%±2.66%) (t[df=60] =-5.396; 95% confidence interval [CI]: -1.66%, -0.76%; P<0.001) and significant change in the Argenta Clinical Classification categories (P<0.001) after physiotherapy intervention. There was a reduction of approximately 10% in infants classified with significant plagiocephaly when the mCVAI cutoff point increased by 1%.Conclusion: Characteristics of Australian infants presenting with plagiocephaly, brachycephaly, and combined conditions were similar to other reports. Infants with positional head deformities can benefit from physiotherapy intervention. The cutoff point of mCVAI at -6% is proposed to be appropriate for the provision of ongoing physiotherapy service.Keywords: plagiocephaly, brachycephaly, modified cranial vault asymmetry index, cutoff point